La Plata sale a escena - Grossman, Luis J. (2000)
Teatro Argentino de La Plata por los arqs. <Bares-García-Germani-Rubio-Sbarra-Ucar>
Keywords: ARGENTINA; BUENOS AIRES; LA PLATA; TEATROS; BARES, ENRIQUE; GERMANI, ROBERTO; GARCÍA, TOMÁS; RUBIO, INES; SBARRA, ALBERTO; UCAR, CARLOS